FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA COMPLAINT HANDLING OFFICER (CHO) DI UNIT KERJA CALL CENTER TELKOMSEL MAKASSAR - Usman Tamrin; Halim Halim; Syarif Ahmad (Politeknik STIA LAN Makassar, 2018)
Abstract Complaint Handling Officer (CHO) must perform according to the Key Performance Indicator (KPI) set by the company and to this day the Telkomsel Makassar Call Center CHO can successfully achieve the set targets. The purpose of this study is to determine the factors that influence the performance of the Complaint Handling Officer in the Telkomsel Call Center work unit. The research method used is quantitative associative method. This method is used to test whether there is influence fromPersonal Factor, Leadership Factor, Team Factor, System Factor, Contextual / Situational Factor to Performance Complaint Handling Officer at Call Center Unit Telkomsel Makassar. Methods of data analysis of this study are applying normality test, regression analysis, and hypothesis test with the help of SPSS version 21. Partial research results, the relationship of personal factors have no positive and significant effect on the performance of CHO with probability value is 0.592. leadership factors do not have a positive and significant effect on the performance of CHO with a probability value of 0.910. there is a positive and significant influence of team factor on CHO performance with probability value is 0,014. system factor has no positive and significant effect on performance with probability value that is 0,650. there is no positive and significant influence of environmental factor on CHO performance with probability value is 0,878. Simultaneously (F test) all independent variables are personal, leadership, team, system, contextual / situational no significant and significant to CHO performance, with probabiltas value (sign) 0.052. It can be said that personal, leadership, team, system and contextual / situational factors together do not affect CHO performance.